Acute toxicity and outcome among pediatric allogeneic hematopoietic transplant patients conditioned with treosulfan-based regimens. (3rd July 2020) - Huttunen, Pasi; Taskinen, Mervi; Vettenranta, Kim
Abstract: Treosulfan-based regimens constitute a feasible and increasingly used, but still myeloablative, conditioning in pediatric allogeneic hematopoietic stem cell transplantation (HSCT). We retrospectively analyzed the acute toxicity and outcome of all consecutive (2004–2015) pediatric HSCT patients prepared for HSCT with treosulfan in a single-center setting. We included HSCTs performed for both nonmalignant ( n = 23) and malignant diseases ( n = 11). The controls were patients with nonmalignant diseases or hematological malignancies conditioned with cyclophosphamide (Cy)-total body irradiation (TBI)-based (39 patients) or busulfan-based regimens (11 patients). The major toxicities of the treosulfan-based regimens were limited to oral mucosa and skin. 50% of the patients needed IV morphine for severe mucositis compared to 31% in patients conditioned with Cy-TBI ( P = 0.02). Other toxicities were rare. The disease-free survival (DFS) of patients transplanted for nonmalignant disorders was 88.9 ± 7.5% at 2 years. The event-free survival (EFS) at 2 years in this small cohort for those with a malignant disease and a treosulfan-based conditioning was 54.5 ± 1.5%. We conclude that a treosulfan-based conditioning regimen gives excellent DFS in pediatric HSCT performed for a nonmalignant disorder but with substantial mucosal toxicity. In a malignant disorder a treosulfan-based regimen looks promising but larger, preferably randomized, studies are needed to prove efficacy.